Ultrasonic based differential diagnosis of renal cysts - Mukhtiar Ahmed Abro; Amanullah; Abdul Ghani Shaikh; Abdul Haleem Shaikh (Gomal Journal of Medical Sciences, 2012)
Background: Renal masses can be broadly categorized into cysts, tumors and inflammatory lesions. Although simple cysts are usually asymptomatic, they occasionally cause flank or abdominal pain, a palpable abdominal mass or hematuria. This study was conducted to see the role of ultrasonography in evaluation of renal cysts.